Individual predictors of adolescent adjustment to maternal cancer: The role of perceived stress, coping, social support, attachment, and self‐efficacy. Issue 2 (30th October 2018) - Rodriguez, Leonor; Groarke, AnnMarie; Dolan, Pat
Abstract: Background: Cancer is among the leading causes of morbidity and mortality around the world. The National Cancer Registry of Ireland reported in 2015 that there were 9312 new cases of female cancers per year, breast cancer being the most common type diagnosed. Research has identified that parental cancer is a stressful situation that can have a strong impact on adolescents' lives; however, some adolescents can turn a negative event into a way of enhancing their skills and psychological resources. This variability needs to be explored further to identify how individual differences contribute to different adjustment experiences for adolescents whose mothers are diagnosed with cancer, namely differences in adolescent coping, self‐efficacy, social support, life satisfaction, and attachment. Aim: The objective of this study was to examine the relative impact of perceived stress, coping, perceived social support, maternal attachment, and self‐efficacy on adolescent adjustment (mood and life satisfaction). Method: Data was collected from 40 adolescents within 38 months of a maternal cancer diagnosis. They completed online questionnaires assessing perceived stress, coping, perceived social support, attachment, self‐efficacy, and adjustment (life satisfaction, negative affect, positive affect, depression, and anxiety). Results: Hierarchical regression analyses showed that perceived stress and coping were the strongest predictors of adjustment explaining variance on all adjustment indices. Maternal attachment, perceived social support, and self‐efficacy were less powerful predictors of adjustment. The model, however, failed to explain any variance on depression and anxiety. Moderation analyses revealed that social support moderated the relationship between perceived stress and positive affect for adolescents with high levels of perceived social support. Conclusions: Findings show that lower perceived stress and positive coping were the best predictors of adjustment in adolescents facing maternal cancer. Results suggest that adolescents could be screened for levels of perceived stress and coping style to identify adolescents who are at risk of poor adjustment when they are adjusting to maternal cancer.